2006
DOI: 10.1099/jmm.0.46206-0
|View full text |Cite
|
Sign up to set email alerts
|

Virulence profile of strains of Cryptococcus neoformans var. grubii evaluated by experimental infection in BALB/c mice and correlation with exoenzyme activity

Abstract: To evaluate the virulence profile of strains of Cryptococcus neoformans var. grubii, 62 strains of this yeast were inoculated into BALB/c mice. It was found that 69 % of the strains were significantly more lethal to the mice and were recovered from a higher percentage (60 %) of the organs compared with the other 31 % of the strains, which were recovered from 35 % of organs tested. Those strains that provoked higher death rates were also recovered from the central nervous system at a higher rate (84 %) than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
(27 reference statements)
1
21
0
2
Order By: Relevance
“…In several reports, the pathogenicities of strains of C. neoformans have been compared by observing experimental infections in mice following intravenous or intracerebral challenge (2,7,14,19,39). However, mammals develop cryptococcosis by inhaling infectious propagules from the environment, and the abilities to survive, proliferate as yeasts, and establish a nidus in the lungs are crucial for the successful development of cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several reports, the pathogenicities of strains of C. neoformans have been compared by observing experimental infections in mice following intravenous or intracerebral challenge (2,7,14,19,39). However, mammals develop cryptococcosis by inhaling infectious propagules from the environment, and the abilities to survive, proliferate as yeasts, and establish a nidus in the lungs are crucial for the successful development of cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have experimentally tested the pathogenicity of environmental isolates of C. neoformans, and none have compared the virulence of clinical and environmental isolates with the same genotypes. In 2006, Silva et al compared the virulence of 62 strains of serotype A that were isolated from pigeon excreta in Brazil (39). Using an intravenous mouse model of experimental cryptococcosis, they observed that the environmental strains varied in their abilities to cause disease; some mice developed symptoms of cryptococcosis, but others remained asymptomatic (39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the LSD test effectively Of all isolates, 91% killed most experimental animals by day 24 postinfection. According to the data of Silva et al (2006a), all strains studied that killed most animals in 24 days were considered highly virulent (69% of 62 strains). Other reports have suggested that C. neoformans var.…”
Section: Discussionmentioning
confidence: 99%
“…(CASADEVALL e PERFECT, 1998), apresentando um tropismo pelo sistema nervoso central que é fator determinante do óbito em infecção experimental (CASADEVALL e PERFECT, 1998;SILVA et al, 2006). Duas variedades são conhecidas: var.…”
Section: é O Agente Etiológico Da Criptococose Que Atinge Pacientes unclassified